2022
DOI: 10.3390/biology11010101
|View full text |Cite
|
Sign up to set email alerts
|

Additional Blue LED during Cultivation Induces Cold Tolerance in Tomato Fruit but Only to an Optimum

Abstract: Tomato is a chilling-sensitive fruit. The aim of this study is to examine the role of preharvest blue LED lighting (BL) to induce cold tolerance in ‘Foundation’ tomatoes. Blue and red supplemental LED light was applied to achieve either 0, 12 or 24% additional BL (0B, 12B and 24B). Mature green (MG) or red (R) tomatoes were harvested and cold stored at 4 °C for 0, 5, 10, 15 and 20 d, and then stored for 20 d at 20 °C (shelf life). Chilling injury (CI) indices, color and firmness, hydrogen peroxide, malondialde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Under 120 mM NaCl salinity stress, both the growth and yield of Silybum marianum reduce sharply in all genotypes collected from diverse ecozones [84]. Plant chilling injury (CI) is caused by a series of events, starting with a slight increase in cell membrane viscosity, followed by an increase in ROS leading to further membrane dysfunction, protein oxidation, inhibition of enzymatic activity, and DNA and RNA damage [85]. Importantly, changes in the redox state of plants lead to changes in thiol protein (SH-group) patterns, which in turn generate metabolic perturbations [86].…”
Section: Asa Relieves Oxygen Pressure Induced By Environment Changes ...mentioning
confidence: 99%
“…Under 120 mM NaCl salinity stress, both the growth and yield of Silybum marianum reduce sharply in all genotypes collected from diverse ecozones [84]. Plant chilling injury (CI) is caused by a series of events, starting with a slight increase in cell membrane viscosity, followed by an increase in ROS leading to further membrane dysfunction, protein oxidation, inhibition of enzymatic activity, and DNA and RNA damage [85]. Importantly, changes in the redox state of plants lead to changes in thiol protein (SH-group) patterns, which in turn generate metabolic perturbations [86].…”
Section: Asa Relieves Oxygen Pressure Induced By Environment Changes ...mentioning
confidence: 99%
“…Also, it is highlighted future research focus, considering the understanding of how light stimuli affect several features of cut flowers and investigating the reaction among species and cultivars (Horibe). Recent work has indicated that by applying specific treatments during the cultivation, quality can be improved (Affandi et al, 2020(Affandi et al, , 2022Min et al, 2021). The results of the study by Terfa et al show that increased blue light during preharvest improved stomatal function under high RH conditions.…”
Section: Preharvestmentioning
confidence: 99%
“…Blue light did not affect the activity of CAT or content of total ascorbic acid. The chilling tolerant tomatoes lost the red color faster which may indicate that the antioxidant lycopene scavenged ROS (Affandi et al, 2022). In basil, we found that both a low (9 %) and a high (90 %) percentage of blue light in combination with increased light intensity improved the postharvest chilling tolerance.…”
Section: The Effect Of Blue Light On Chilling Tolerancementioning
confidence: 67%
“…Furthermore, light spectrum can increase the content of antioxidants which may be beneficial during chilling. In tomato, blue light improved the chilling tolerance, which was presumable due to an increase of the antioxidant lycopene (Affandi et al, 2022). However, in anthurium cut flowers postharvest blue or white compared to darkness, red or red blue (70:30) light increased the CI due to an increase in water loss (Aliniaeifard et al, 2020).…”
Section: Light and Chilling Tolerancementioning
confidence: 99%
See 1 more Smart Citation